Lantibiotics : Synthesis and Antimicrobial activity - Sookkhee, Siriwoot; Sakonwasun, Choompone (Biomedical Sciences and Clinical Medicine, 2017)
Lantibiotic is the antimicrobial peptides that most of them were produced from a member of lactic acid bacteria. It is classi fi ed into class I of bacteriocin. The important peptides are nisin, lacticin 3147, and subtilin. Its propeptide consists of the lantionine or methyllantionine structures which formed during the post-translational modi fi cation. It is broad spectrum against the various groups of bacteria. Mechanism of action depends on its type and peptide property. Currently, some lantibiotics possess the potential to apply for eradicating the antibiotic-resistant pathogens that may be reduced the drug resistant problem. The present article proposes about the synthesis step and antimicrobial activity of lantibiotic and includes about the potentials for further application in the medical aspects.